Mitigation and models for determining premiums for natural disaster insurance due to excessive rainfall. Issue 1 (January 2021) - Kalfin,; Sukono,; Supian, S; Mamat, M
Abstract: Natural disasters due to excessive rainfall often cause huge losses in the form of impacts including casualties and economic losses. To minimize casualties, disaster mitigation is needed, while financing for disasters (emergency response) and financing after disasters (rehabilitation and reconstruction) can be carried out with insurance. This paper aims to determine mitigation efforts and insurance premiums for natural disasters. The method as a mitigation effort is studied based on several methods that are suitable for the conditions of the community in areas that are often affected by disasters. Meanwhile, regarding loss insurance, the premium is calculated based on the number of cases, the rate set by the insurance company and the amount insured (loss). Based on the results of natural disaster mitigation studies, it is necessary to adjust it to the type of disaster. In the case of landslides, housing buildings must be standardized, while in cases of flooding, river normalization is required. Mitigation in general, namely the installation of disaster sirens and disaster response training. Regarding loss insurance, it is found that the optimal premium for the government and insurance companies is obtained.